Gruberi bursitis in rheumatic patients with foot and ankle pain: a retrospective sonographic study - Todorov, Plamen; Mekenyan, Lili; Levterova, Boryana; Batalov, Anastas (Frontiers in Medicine, 2025)
IntroductionFoot and ankle pain is a common problem in rheumatic patients. One often underrecognized cause of this complaint is Gruberi (or subtalar) bursitis. The Gruberi bursa is a structure that originates from the sinus tarsi and extends over the dorsal talar surface. It reduces the friction of the extensor digitorum longus tendon over the convex contour of the head of the talus. On ultrasound, Gruberi bursitis is characterized by a well-defined fluid collection in the dorsolateral foot, located between the talus and the tendon of the extensor digitorum longus. Our study aimed to determine the frequency of Gruberi bursitis in patients with various rheumatic diseases who presented with foot and ankle pain at our institution and to describe its sonographic features in detail.Materials and methodsA descriptive, observational, retrospective study was conducted on patients over 18 years old who visited a tertiary university hospital between 1 July 2022 and 31 December 2023. Details regarding the patients’ medical history, age, gender, and primary rheumatic disease were obtained from their medical records. Descriptive statistics were utilized to present the data.ResultsOf the 608 patients examined for foot and ankle pain at our institution during the study period, 78 cases of Gruberi bursitis were identified in 63 patients. The average age of the participants was 61.7 years (range: 25–85 years), and 71% (n = 45) of the participants were women. The sonographic features of Gruberi bursitis included a monocular, anechoic fluid collection typically located between the extensor digitorum longus tendon and the dorsolateral surface of the head of the talus. The mean largest dimension of fluid collections in the oblique plane (from the sinus tarsi and across the dorsal talus) was 16 mm (range: 8–29 mm).ConclusionGruberi bursitis is easily identifiable through ultrasound due to its characteristic location and appearance. In total, we identified this condition in 9% of our rheumatic patients with foot and ankle pain.